2022
DOI: 10.1039/d2ay00181k
|View full text |Cite
|
Sign up to set email alerts
|

Whispering gallery mode resonators in continuous flow: spectral assignments and sensing with monodisperse microspheres

Abstract: Whispering gallery mode resonator (WGMR) microspheres yield highly structured optical spectra that are extremely sensitive to their environment and are of intense interest for use in a variety of sensing...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…More operational details are available in video S3 and video S4. These two situations could both find useful applications in practical applications, for example, to eliminate undesired target (by strong ballistic shooting) or to install tiny mechanical payload for sensing [41] or deliver medicine or genetic cues [15,42]. To further exemplify this functionality, a simple bio-target shooting was carried out, where a sideflipped algal cell (15 μm wide and 20 μm long) was selected as the target, sitting 55 μm away from the slingshot.…”
Section: Directional Shooting Operationmentioning
confidence: 99%
“…More operational details are available in video S3 and video S4. These two situations could both find useful applications in practical applications, for example, to eliminate undesired target (by strong ballistic shooting) or to install tiny mechanical payload for sensing [41] or deliver medicine or genetic cues [15,42]. To further exemplify this functionality, a simple bio-target shooting was carried out, where a sideflipped algal cell (15 μm wide and 20 μm long) was selected as the target, sitting 55 μm away from the slingshot.…”
Section: Directional Shooting Operationmentioning
confidence: 99%
“…Different reagents can be pumped through to study the interaction between antibodies and proteins expressed by cancer cells. Lilley et al recently reported a continuous flow technique for measuring active dye-doped WGM microspheres suspended in solution, and a clustering algorithm was developed to analyze the results and differentiate signals from two different sizes of microspheres . In both cases, an external pump was required for operation, which is not ideal for POC or remote sensing.…”
Section: Introductionmentioning
confidence: 99%